Block backstepping design of nonlinear state feedback control law for underactuated mechanical systems - Ru, Shubhobrata; Barai, Ranjit Kumar; Maitra, Madhubanti (Springer, 2016)
This book presents a novel, generalized approach to the design of nonlinear state feedback control laws for a large class of underactuated mechanical systems based on application of the block backstepping method. The control law proposed here is robust against the effects of model uncertainty in dynamic and steady-state performance and addresses the issue of asymptotic stabilization for the class of underactuated mechanical systems. An underactuated system is defined as one for which the dimension of space spanned by the configuration vector is greater than that of the space spanned by the control variables. Control problems concerning underactuated systems currently represent an active field of research due to their broad range of applications in robotics, aerospace, and marine contexts. The book derives a generalized theory of block backstepping control design for underactuated mechanical systems, and examines several case studies that cover interesting examples of underactuated mechanical systems. The mathematical derivations are described using well-known notations and simple algebra, without the need for any special previous background in higher mathematics. The chapters are lucidly described in a systematic manner, starting with control system preliminaries and moving on to a generalized description of the block backstepping method, before turning to several case studies. Simulation and experimental results are also provided to aid in reader comprehension.